Production of Biodiesel from Castor Oil Using Egg Shell Waste as Solid Catalysts - Nur Farzana, Omar (2012)
The increase in price of petroleum and environmental concerns, the search for alternative fuels has gained importance. Biodiesel is one of several alternative fuels that is renewable and can be manufactured from vegetable oils. Biodiesel's physical properties are similar to those of petroleum diesel, but it is a cleaner-burning alternative. Using biodiesel in place of petroleum diesel can reduce emissions. The main objectives of the research is to produce biodiesel from castor oil using activated egg shell waste as solid catalysts and to investigate the effect of methanol/oil ratio, temperature and reaction time on the biodiesel yield. The effect of parameters on the biodiesel yield has been investigated from the reaction process that is called transterification process. Biodiesel has been successfully produced from castor oil using activated egg shell waste as solid catalyst by the variation of methanol/oil ratio, temperature and reaction time has affected the biodiesel yield. The highest biodiesel yield was found by the methanol/oil ratio of 5:1, temperature of 55°C and reaction time of 4 hours.